There is More to the Teaching and Learning of Mathematics Than the Use of Local Languages: Mathematics Teacher Practices - Nancy Chitera; Dun Kasoka; E. Thomo (Journal of Education and Learning (EduLearn), 2016)
In this article, we present a discussion about the type of mathematical discourse that is being produced in classrooms where the language of learning and teaching is local languages.  We also further explore the tensions in the mathematical discourse being produced. The study sample was 4 mathematics teachers from a semi-urban primary school in Malawi. The methods of data collection included classroom observations, pre-observation focus group discussions and reflective interviews. The results show that even though both students and teachers were able to communicate freely in local languages in the mathematics classroom, the mathematical discourse that came was distorted. This is mainly caused by lack of a well-developed mathematical discourse in local languages, which in turn takes away the confidence of mathematics teachers in the classroom. As a result, the mathematics classrooms are still being characterized by teachers not being creative, use of word by word from books, focus more on procedural than conceptual and thus teacher centered is still dominant in these classrooms. Furthermore, it is found that there are tensions between the formal and informal mathematical language in local languages. These results in turn have promoted a more in-depth understanding to the teaching and learning of mathematics when local language is the language of learning and teaching. Therefore, this article argues for a well-balanced approach when it comes to teaching and learning of mathematics rather than just focusing on the use of local languages.